Trends in the Development of China’s Trade Diplomacy in Promoting National Interests on the World Stage - Odil qizi, Egamberdieva Malika (RA Journal of Applied Research, 2022)
Today, relations between China and the rest of the world are entering a new phase. China’s economic miracle was fueled by industry and investment, but today domestic consumption is the main driver of growth. The country is becoming less open economically to the rest of the world. However, the rest of the world is becoming increasingly open to the impact of China, which is the world’s second-largest economy and its leading trading nation. These changes are accompanied by trade tensions and growing protectionism in many countries. Since China decided to open up its economy to the rest of the world and took part in large-scale reforms, it has become a real global force.